How can we improve models of care in inflammatory bowel disease? An international survey of IBD health professionals. (1st December 2014) - Mikocka-Walus, Antonina; Andrews, Jane M.; Rampton, David; Goodhand, James; van der Woude, Janneke; Bernstein, Charles N.
Abstract: Background and aims: Few studies have specifically examined models of care in IBD. This survey was designed to help gather information from health professionals working in IBD services on current care models, and their views on how to best reshape existing models for IBD care worldwide. Methods: An online mixed-methods survey was conducted with health professionals caring for IBD patients. Recruitment was conducted using the snowballing technique, where members of professional networks of the investigators were invited to participate. Results of the survey were summarised using descriptive statistics. Results: Of the 135 included respondents, 76 (56%) were female, with a median age of 44 (range: 23–69) years, 50% were GI physicians, 34% nurses, 8% psychologists, 4% dieticians, 2% surgeons, 1% psychiatrists, and 1% physiotherapists. Overall, 73 (54%) respondents considered their IBD service to apply the integrated model of care, and only 5% reported that they worked exclusively using the biomedical care (no recognition of psychosocial factors). The majority of respondents reported including mental health assessment in their standard IBD care (65%), 51% believed that an ideal IBD service should be managed in specialist led clinics, and 64% wanted the service to be publicly funded. Respondents pictured an ideal IBD service as easy-access fully multi-disciplinary, with a significant role for IBD nurses and routine psychological and nutritional assessment and care. Conclusions: Health care professionals believe that an ideal IBD service should: be fully integrated, involve significant roles of nurses, psychologists and dieticians, run in specialist clinics, be easily accessible to patients and publicly funded.